INCREASING CLINICAL PRECEPTOR COMPETENCE THROUGH PRECEPTORSHIP METHOD TRAINING IN BANGIL HOSPITAL, PASURUAN REGENCY - Sholihatul Amaliya; Rinik Eko Kapti; Muladefi Choiriyah; Efris Kartika Sari; Ikhda Ulya; Ika Setyo Rini (Caring : Jurnal Pengabdian Masyarakat, 2022)
The Preceptorship method facilitates students to develop their cognitive, affective, and psychomotor abilities. Through Preceptorship, clinical instructors/preceptors become role models as tutors, leaders, supervisors, and mentors for students. Furthermore, nursing staff who meet the qualifications of a preceptor need Preceptorship training. The Pasuruan District Hospital is one of the network hospitals where nursing students practice the nursing profession, and there are only a few preceptors have attended Preceptorship training. Therefore, it is necessary to conduct Preceptorship training for preceptors. This activity aims to achieve preceptor competence with the Preceptorship method. The respondents were health care staff from Bangil Hospital, such as nurses, midwives, nutritionists, radiographers, medical recorders clerks, and physical therapists. The activity included training for three days from 19-21 November 2019 by providing material, demonstrating, and simulating the Preceptorship method in several rooms at Bangil Hospital. The data collection to measure the level of knowledge used pre-test and post-test questionnaires, while for skills using observation in the implementation of simulations directly to students in the hospital room. Forty-seven respondents participating in this training were male (32%) and female (68%). The results of the level of knowledge were pre-test mean 47.74 and post-test 88.85 with p-value paired t-test results 0.001. Observation results show that the preceptor can practice the Preceptorship method well with students. In conclusion, this training activity increases the knowledge and skills of Preceptorship clinical education methods for preceptors.